The Relationship Between Maternal Age And The Incidence Of Low Birth Weight Babies - Sroja Ade Putri; Julia Herdiman (Sean Institute, 2023)
The Riau Province health profile (2020) shows that the biggest cause of neonatal death is low birth weight babies (LBW). This is supported by national data (RISKESDAS 2019). One of the factors considered to be contributing to the high prevalence of low birth weight babies in Indonesia is the age of the mother. The purpose of the study : To determine the relationship between maternal age and the incidence of low birth weight in pregnant women at Selasih Pangkalan Kerinci Regional Hospital, Pelalawan District, Riau. Method: This an analytic research with a cross-sectional design. Samples were taken using a non-probability consecutive sampling from medical record in 2020-2021 . The number of respondents obtained was 93 and a chi square test was carried out. Results : Respondents who were <21 years of age experienced the most low birth weight events, namely 19 people (20.4%). Respondents aged 21-34 years showed that as many as 17 respondents (18.2%) experienced low birth weight. Respondents who were >35 years old showed that 22 people or 23.6% experienced low birth weight. Based on Chi-Square Tests, a relationship was found between maternal age and low birth weight babies with a p-value of 0.003 (p value <0.05). The results of the study from 93 research samples found that 58 mothers (62.4%) gave birth to babies with low birth weight and 35 mothers (37.6%) did not. Conclusion: A significant relationship was found between age of pregnant women and the incidence of low birth weight babies at Selasih Pangkalan Kerinci Regional Hospital.